Human Object Counter Tracking Using Connected Component Labelling On Digital Image Processing - Fitri Lestari; Erwin Dwik Putra; Anisya Sonita; Yulia Darnita (Jurnal Komputer, Informasi dan Teknologi, 2023)
Object tracking is usually used to determine the position of objects and environmental conditions around these objects. Objects that require supervision in order to run properly require a system to monitor the object. Every movement of the object will be known directly through the camera image. So in this study a system was created to detect and track objects. Implementing an object detection system based on image processing using the connected component labeling method. Then displaying the detection results on the divided image frame. Moving object detection and tracking The algorithm used to detect and track moving objects is connected component labeling. Based on the analysis of the workings of the connected component labeling algorithm for detecting and tracking moving objects using video, it can be concluded that the connected component labeling algorithm has succeeded in tracking and labeling each object based on the position and number of objects, even though they look erratic, in human movement.